Powołanie i przygotowanie do służby misyjnej wiernych Kościoła Jezusa Chrystusa Świętych w Dniach Ostatnich (mormonów) - Anoszko, Sergiusz (Annales Missiologici Posnanienses, 2019)
Serving on a mission is almost an indispensable part of the image of the adherents of the Church of Jesus Christ of Latter-day Saints, commonly known as Mormons, quasi-Christian new religious movement. The next text attempts to analyse and take a closer look at the theme of calling and preparing for the ministry of being a missionary as an attribute of this Church that was founded by Joseph Smith. Starting from an upbringing in the family and social expectations of the Church’s members through education in the Missionary Training Center, we can follow the vocation path and the creative process of the future Mormon missionary who preach the Gospel in various corners of the world. Missionary ministry is important in the life of each Mormon believer, even those who didn’t serve as a missionary, because it leaves a lasting imprint and affects the minds of the members of this new religious group for the rest of their lives.